Are Cape gannets dependent upon fishery waste? A multi‐scale analysis using seabird GPS‐tracking, hydro‐acoustic surveys of pelagic fish and vessel monitoring systems. Issue 3 (7th May 2013) - Tew Kai, Emilie; Benhamou, Simon; van der Lingen, Carl D.; Coetzee, Janet C.; Pichegru, Lorien; Ryan, Peter G.; Grémillet, David
Summary: Climate change and fishing impact marine ecosystems, potentially modifying the availability of small pelagic fish to marine top predators. Some seabirds that primarily rely upon these resources have switched to feeding on fishery waste. It has therefore been argued that seabirds might become dependent upon this artificial resource. To test this hypothesis, we studied the foraging behaviour of Cape gannets Morus capensis breeding off the coast of South Africa using high‐resolution Global Positioning System‐tracking in relation to the availability of pelagic fish assessed by acoustic at‐sea surveys, and fishing effort by the two main south African fisheries (purse seiners that compete with seabirds for pelagic fish, and demersal trawlers that process fish at sea and discharge fish waste) tracked with vessel monitoring systems. Conjoint seabird, fish and fisheries information were analysed at mesoscale ( c . 100 km) and sub‐mesoscale ( c . 10 km) in years of high (2002), medium (2009) and low (2005) pelagic fish biomass within gannets' foraging range. We found substantial inter‐annual variability in spatial use by breeding gannets, which was driven primarily by pelagic fish availability. At the mesoscale, birds and purse seiners exploited similar marine areas, but no fine‐scale dependence of birds on purse seiners was detected. Crucially, fine‐scale dependence of gannets upon trawlers producing fishery waste was only detected in 2005, when pelagic fish biomass was lowest, indicating a direct effect of trawlers on gannet foraging behaviour in the absence of natural prey. Further overlap analyses of gannet and trawler foraging areas during 2002–2010 confirmed that breeding birds only seek trawlers when pelagic fish availability is low, strongly suggesting reversible seabird dependency upon fishery waste. Synthesis and applications . Our study demonstrates that seabirds such as Cape gannets depend on fishery waste when their natural prey is scarce, but revert to feeding on natural resources whenever available, showing highly flexible foraging behaviour. These results have important implications in the context of the anticipated legislation banning at‐sea disposal of fishery waste in different regions, including European seas, highlighting the necessity to concomitantly promote sustainable fishing allowing the restoration of pelagic fish stocks. Abstract : Our study demonstrates that seabirds such as Cape gannets depend on fishery waste when their natural prey is scarce, but revert to feeding on natural resources whenever available, showing highly flexible foraging behaviour. These results have important implications in the context of the anticipated legislation banning at‐sea disposal of fishery waste in different regions, including European seas, highlighting the necessity to concomitantly promote sustainable fishing allowing the restoration of pelagic fish stocks.